The relation between anxious personality traits and fear generalization in healthy subjects: A systematic review and meta-analysis - Sep, Milou S.C.; Steenmeijer, Anna; Kennis, Mitzy (Neuroscience and biobehavioral reviews, 2019)
•19 studies on the relation between anxious traits and fear generalization were identified.•Meta-analysis established a significant small positive correlation.•No moderating effect of age, sex, study quality, fear generalization paradigm or measurement type was found.•Trait anxiety may increase vulnerability to anxiety disorders by increasing fear generalization.•Future prospective studies are necessary to determine directionality of this effect. Anxious personality characteristics form a risk factor for anxiety disorders. A proposed mechanistic pathway is that anxious personality could lead to greater vulnerability by increasing fear generalization. Here, we investigate if there is evidence for this relationship before the onset of pathological anxiety, with a meta-analysis in healthy subjects. Our search (anxious personality & fear generalization) was performed in PubMed, PsychInfo, and Embase and via snowballing. In total, 4892 studies were screened and 19 studies (1348 participants) were included in the current review (meta-analysis: 18 studies, 1310 participants). The meta-analysis showed a significant, small, positive relationship between anxious personality and fear generalization (r = .19, 95%CI [.126, .260], p <.001). No moderators of the relationship were identified. The identified robust relation suggests that people who score high on anxious personality have a somewhat stronger tendency to generalize fear to safe or novel situations. This might explain their vulnerability to anxiety disorders mechanistically, yet future (prospective) studies are warranted to confirm the hypothesized directionality of this effect.